Cluster Analysis Using the Physical Condition Endurance Method for Archery Sports - Pratama, Octavian Serka Yudha; Wibowo, Tito parta; Sina, Ibnu; Wattimena, Ferry Yohannes (Mamaos: Journal Physical Education, Sport and Art, 2025)
The development of archery achievements in Indonesia so far has not been able to reach the limits of the Olympics and the development of achievements in Indonesia only focuses on the national level and on the Asian scale due to several factors, including the lack of infrastructure for archery because the infrastructure includes a fairly large field, for example the field. football or red soil whose ground must be level. As well as management management which is still less focused on developing archers in the regions, especially in Indonesia. There is a lot of archery in Indonesia that needs to be addressed both in terms of management and infrastructure, including in areas that lack knowledge of sport science and good management, with the existence of sport science in Indonesia and good management of sports, especially archery in Indonesia, this can change aspects of archery. the lack of achievement becomes the number of achievements so that archery in Indonesia can compete in the Olympic championship and gain good achievements. With this method of physical condition exercise, it can be used properly and correctly to add insight into the media used. The method used is using cluster analysis using the Physical Condition Endurance Method for Archery.